STRATEGI MASYARAKAT KOMPLEK LOKALISASI DANARASA SLARANG DALAM MEMBENTUK KELUARGA SAKINAH - Samsul Hidayat; Moh. Iljam (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2023)
This research aims to find out the strategies used by the community of the Danarasa Slarang localization complex in forming a sakinah family. This type of research is field research (field research). The research approach used is a qualitative approach. The variable in this research is the dependent variable, namely the strategy of the Danarasa Slarang localization complex community in forming a sakinah family. The research subjects in this study were 3 families drawn from the community of the Danarasa localization complex, Slarang village, Kesugihan District, Cilacap Regency. The data collection methods used were documentation, interviews and observation. Data analysis procedures are carried out using data reduction methods, data presentation, and data evaluation or conclusion. Based on the results of the analysis, it was concluded that the strategy carried out by the people of the Danarasa Slarang localization complex was aimed at one goal, namely to form a sakinah family. The author concludes that they have understood the sakinah family and are able to form a sakinah family.